2009
DOI: 10.1159/000251181
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Percutaneous Nephrolithotomy in Children Having Complex Stones

Abstract: Objectives: To review our experiences with percutaneous nephrolithotomy in children with complex renal calculi. Patients and Methods: We retrospectively analyzed the records of 31 children with complex renal calculi who were treated by percutaneous nephrolithotomy at 2 hospitals of our university between June 2003 and June 2008. The mean age of the patients was 10.4 years (range 22 months to 15 years). Three patients were aged ≤5 years. Stone clearance and complications were recorded. Results: The mean operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…Factors affecting PNL success rates were examined by Goldwasser et al and the authors reported that the size of the stone and its localization mostly affected the success rates [ 16 ]. Consistent with the literature, in terms of stone localization, we also found that the success rate in complex stones was lower than that in simple stones [ 7 , 17 , 18 , 19 , 20 ]. Our success rate in simple stones was 96.7% (single stone in pelvis or a calyx), but 45.5% in complex stones ( p < 0.001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Factors affecting PNL success rates were examined by Goldwasser et al and the authors reported that the size of the stone and its localization mostly affected the success rates [ 16 ]. Consistent with the literature, in terms of stone localization, we also found that the success rate in complex stones was lower than that in simple stones [ 7 , 17 , 18 , 19 , 20 ]. Our success rate in simple stones was 96.7% (single stone in pelvis or a calyx), but 45.5% in complex stones ( p < 0.001).…”
Section: Discussionsupporting
confidence: 91%
“…We thought that multiple working channels could increase the complication rates, so we created a single subcostal channel for all of our patients. The reported success rates in complex stones ranged from 61% to 89% with the use of multiple channels [ 7 , 17 , 18 , 19 , 20 ]. Netto et al reported that the success of percutaneous treatment for staghorn calculi is highly related to optimal kidney access with supracostal and multiple access approaches, despite a slight increase in the incidence of acceptable complications [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure can be prevented by using ultrasound guidance [27]; however, to our knowledge there are no reports in the literature regarding the use of ultrasound-guided PNL in infants and very young children. Similar studies reported the use of fluoroscopy in children [6,7,13,28].…”
Section: Discussionsupporting
confidence: 59%
“…Age, sex, BMI, stone size, operation time, success rate, postoperative nephrostomy tube placement, preoperative urine culture, pelvic urine culture and stone culture were compared between groups I and II. Statistical analysis with 2 for qualitative variables and Mann-Whitney U test for quantitative variables was considered significant at p ! 0.05.…”
Section: Methodsmentioning
confidence: 99%